VJ Segment Usage of TCR-Beta Repertoire in Monozygotic Cystic Fibrosis Twins - Fischer, Sebastian; Stanke, Frauke; Tümmler, Burkhard (Frontiers in Immunology, 2021)
Sixteen monozygotic cystic fibrosis (CF) twin pairs of whom 14 pairs were homozygous for the most common p.Phe508del CFTR mutation were selected from the European Cystic Fibrosis Twin and Sibling Study Cohort. The monozygotic twins were examined in their T cell receptor (TCR) repertoire in peripheral blood by amplicon sequencing of the CDR3 variable region of the ß-chain. The recruitment of TCR J and V genes for recombination and selection in the thymus showed a strong genetic influence in the CF twin cohort as indicated by the shortest Jensen-Shannon distance to the twin individual. Exceptions were the clinically most discordant and/or most severely affected twin pairs where clonal expansion probably caused by recurrent pulmonary infections overshadowed the impact of the identical genomic blueprint. In general the Simpson clonality was low indicating that the population of TCRß clonotypes of the CF twins was dominated by the naïve T-cell repertoire. Intrapair sharing of clonotypes was significantly more frequent among monozygotic CF twins than among pairs of unrelated CF patients. Complete nucleotide sequence identity was observed in about 0.11% of CDR3 sequences which partially should represent persisting fetal clones derived from the same progenitor T cells. Complete amino acid sequence identity was noted in 0.59% of clonotypes. Of the nearly 40,000 frequent amino acid clonotypes shared by at least two twin siblings 99.8% were already known within the immuneACCESS database and only 73 had yet not been detected indicating that the CDR3ß repertoire of CF children and adolescents does not carry a disease-specific signature but rather shares public clones with that of the non-CF community. Clonotypes shared within twin pairs and between unrelated CF siblings were highly abundant among healthy non-CF people, less represented in individuals with infectious disease and uncommon in patients with cancer. This subset of shared CF clonotypes defines CDR3 amino acid sequences that are more common in health than in disease.